Spinal Muscular Atrophy: From Gene Discovery to Clinical Trials. (23rd July 2013) - Nurputra, Dian K.; Lai, Poh San; Harahap, Nur Imma F.; Morikawa, Satoru; Yamamoto, Tomoto; Nishimura, Noriyuki; Kubo, Yuji; Takeuchi, Atsuko; Saito, Toshio; Takeshima, Yasuhiro; Tohyama, Yumi; Tay, Stacey KH; et al.
Summary: Spinal muscular atrophy (SMA) is a common neuromuscular disorder with autosomal recessive inheritance, resulting in the degeneration of motor neurons. The incidence of the disease has been estimated at 1 in 6000–10, 000 newborns with a carrier frequency of 1 in 40–60. SMA is caused by mutations of the SMN1 gene, located on chromosome 5q13. The gene product, survival motor neuron (SMN) plays critical roles in a variety of cellular activities. SMN2, a homologue of SMN1, is retained in all SMA patients and generates low levels of SMN, but does not compensate for the mutated SMN1 . Genetic analysis demonstrates the presence of homozygous deletion of SMN1 in most patients, and allows screening of heterozygous carriers in affected families. Considering high incidence of carrier frequency in SMA, population‐wide newborn and carrier screening has been proposed. Although no effective treatment is currently available, some treatment strategies have already been developed based on the molecular pathophysiology of this disease. Current treatment strategies can be classified into three major groups: SMN2 ‐targeting, SMN1 ‐introduction, and non‐ SMN targeting. Here, we provide a comprehensive and up‐to‐date review integrating advances in molecular pathophysiology and diagnostic testing with therapeutic developments for this disease including promising candidates from recent clinical trials.